(2x+4y)+(2x-y)-(x-2y)=

Simple and best practice solution for (2x+4y)+(2x-y)-(x-2y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+4y)+(2x-y)-(x-2y)= equation:


Simplifying
(2x + 4y) + (2x + -1y) + -1(x + -2y) = 0

Remove parenthesis around (2x + 4y)
2x + 4y + (2x + -1y) + -1(x + -2y) = 0

Remove parenthesis around (2x + -1y)
2x + 4y + 2x + -1y + -1(x + -2y) = 0
2x + 4y + 2x + -1y + (x * -1 + -2y * -1) = 0
2x + 4y + 2x + -1y + (-1x + 2y) = 0

Reorder the terms:
2x + 2x + -1x + 4y + -1y + 2y = 0

Combine like terms: 2x + 2x = 4x
4x + -1x + 4y + -1y + 2y = 0

Combine like terms: 4x + -1x = 3x
3x + 4y + -1y + 2y = 0

Combine like terms: 4y + -1y = 3y
3x + 3y + 2y = 0

Combine like terms: 3y + 2y = 5y
3x + 5y = 0

Solving
3x + 5y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5y' to each side of the equation.
3x + 5y + -5y = 0 + -5y

Combine like terms: 5y + -5y = 0
3x + 0 = 0 + -5y
3x = 0 + -5y
Remove the zero:
3x = -5y

Divide each side by '3'.
x = -1.666666667y

Simplifying
x = -1.666666667y

See similar equations:

| 16-(3x-15)=4x-(9x-9) | | 3=8x-7x+4 | | y^3(3-4x^2)=7x-y^4 | | 2(x+3/4)=9(1/6-x) | | -8x+9x+6=9 | | 6x-8x+2=-13 | | 35=x+(2x-1)+(3(2x-1)+3) | | 35=x+(2x-1)+(3(2x-1)+2) | | 35=x+(3x-1)+(4(3x-1)+2) | | x(x+5)+1=(x+6)(x+6) | | 7=r^(1/2) | | 6x-3-5x=-13-5 | | 2cotx/sinx | | 35=x+(3x-1)+(2(2x-1)+2) | | M/10=4 | | 8x-7x-6=7-13 | | 10(x+2/15)=8(x-7/3) | | 35=x+(2x-1)+(4(2x-1)+2) | | 9x-16=3x+20 | | X/2=50 | | 4x-5=3x-3 | | -5=7x+1-6x | | 35=x+(2x-1)+(14(2x-1)+2) | | 115+5x=240 | | 3.5x+5=50.50 | | -15=-6r-1-2 | | 25x+57=232 | | M^(3/4)=27 | | 15x-17+2x=-34 | | 5x+9-4x=-1 | | 5x-1=4x-4 | | 6+3a+4a=-8 |

Equations solver categories